Green synthesis of silver nanoparticles using rubus rosifolius linn fruit extracts: Characterization, optimization, and application in photocatalytic degradation of dye - Martin, Marilen M. (Animo Repository, 2023)
Rubus rosifolius Linn is a wild raspberry found in the Philippines. The fruit extract is found to be abundant in interesting profiles of antioxidants such as flavonoids, terpenoids, tannins, and polyphenols. In this study, the fruit extracts of sampinit were used as a reducing agent for the synthesis of silver nanoparticles (AgNPs) via a ‘one-pot’ facile approach. Sampinit aqueous fruit extract-AgNPs (SAFE-AgNPs) were synthesized by reducing silver ions using sampinit extract. The optical, chemical, and morphological properties of the SAFE-AgNPs were characterized. Maximal absorption of SAFE-AgNPs was observed at 415 nm, associated with the characteristic surface plasmon resonance profile of AgNPs. SAFE-AgNPs displayed highly stable and homogeneous nanoparticles with a hydrodynamic size of 85.6 ± 0.98 nm and a zeta potential of -29.5 ± 0.96 mV. EDX and XRF analysis showed that SAFE-AgNPs are chiefly composed of silver (Ag) and carbon (C), where C was largely localized on the surface of AgNPs. FTIR analysis showed that SAFE-AgNPs contain key chemical functional groups associated with sampinit-derived phytoconstituents. Significant photocatalytic degradation of methylene blue using SAFE-AgNPs was achieved under sunlight and LED light irradiations at degradation rates of 98.8% and 97.6%, respectively. Overall, the biosynthesized SAFE-AgNPs produced a small, spherical, and monodisperse population which can be a good candidate as a photocatalytic agent for the photodegradation of organic dye pollutants. Furthermore, understanding the general mechanisms of the photocatalysis potential of biogenic AgNPs may provide a novel approach to wastewater treatment and establish SAFE-AgNPs as potent catalysts in the future. Keywords: green synthesis, photocatalysis, photodegradation, Rubus rosifolius Linn, silver nanoparticles